Evaluating Declines in Compliance With Ecological Momentary Assessment in Longitudinal Health Behavior Research: Analyses From a Clinical Trial - Sarah Tonkin; Julie Gass; Jennifer Wray; Eugene Maguin; Martin Mahoney; Craig Colder; Stephen Tiffany; Larry W Hawk Jr (JMIR Publications, 2023)
BackgroundEcological momentary assessment (EMA) is increasingly used to evaluate behavioral health processes over extended time periods. The validity of EMA for providing representative, real-world data with high temporal precision is threatened to the extent that EMA compliance drops over time. ObjectiveThis research builds on prior short-term studies by evaluating the time course of EMA compliance over 9 weeks and examines predictors of weekly compliance rates among cigarette-using adults. MethodsA total of 257 daily cigarette-using adults participating in a randomized controlled trial for smoking cessation completed daily smartphone EMA assessments, including 1 scheduled morning assessment and 4 random assessments per day. Weekly EMA compliance was calculated and multilevel modeling assessed the rate of change in compliance over the 9-week assessment period. Participant and study characteristics were examined as predictors of overall compliance and changes in compliance rates over time. ResultsCompliance was higher for scheduled morning assessments (86%) than for random assessments (58%) at the beginning of the EMA period (P<.001). EMA compliance declined linearly across weeks, and the rate of decline was greater for morning assessments (2% per week) than for random assessments (1% per week; P<.001). Declines in compliance were stronger for younger participants (P<.001), participants who were employed full-time (P=.03), and participants who subsequently dropped out of the study (P<.001). Overall compliance was higher among White participants compared to Black or African American participants (P=.001). ConclusionsThis study suggests that EMA compliance declines linearly but modestly across lengthy EMA protocols. In general, these data support the validity of EMA for tracking health behavior and hypothesized treatment mechanisms over the course of several months. Future work should target improving compliance among subgroups of participants and investigate the extent to which rapid declines in EMA compliance might prove useful for triggering interventions to prevent study dropout. Trial RegistrationClinicalTrials.gov NCT03262662; https://clinicaltrials.gov/ct2/show/NCT03262662